PENGARUH LINGKUNGAN VISUAL RUANGAN KULIAH PADA MOOD MAHASISWA UNTUK MULAI BELAJAR - Leonardo Leonardo (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2022)
Mood is psychological response to many emosional triggers derived from our visual surroundings which mostly perceived from previous visual experiences. Learning atmosphere in college classrooms need to be brought to attention for their potentials to lead students mood when entering classrooms and affect learning process during class hours. This article aims to describe the composition of visual environment elements in classroom. Students mood are recorded, their assessment on attended classrooms are explained, as well as on ARCS to show their learning motives. Outputs confirm that mood is positively affected by lighting and window with exterior view. Thus mood can be made indicator to lighting condition in classrooms as to physical learning atmospheres.